PLATELET-RICH PLASMA THERAPY FOR ERECTILE DYSFUNCTION: A REVIEW OF PRECLINICAL AND CLINICAL STUDIES - A. D. Kaprin; A. A. Kostin; M. V. Epifanova; M. E. Chalyy; E. V. Gameeva; S. A. Artemenko (Исследования и практика в медицине, 2019)
Erectile dysfunction is no longer a psychosocial problem. Nowadays, it is a marker specific for the initial stages of cardiovascular diseases. Рlatelet-rich plasma (PRP) is a new and promising method, which totally deserves to be noted by specialists. To review currently existing pre-clinical and clinical studies concerning application of PRP in erectile dysfunction published in international sources such as PubMed, Cochrane Library, Clinicaltrials.gov. The current data of preclinical and clinical studies determine the absence of PRP side effects and the effectiveness for ED treatment. PRP-therapy is a pathogenetically substantiated method of treating erectile dysfunction. The therapy is designed for repair and regeneration of endothelium, smooth muscle cells, and connective tissue. However, large, placebo-controlled, multicenter studies are needed to creation a systematic review and meta-analysis.